USING AUTHENTIC MATERIALS IN FOSTERING STUDENTS LISTENING COMPREHENSION IN AN EFL CLASSROOM - Dian Ekawati, - (2018)
Authentic materials are considered useful in listening classroom since it can foster students' learning engagement. However, selecting and presenting materials in a listening classroom especially in coping with the difficulties in catching the meaning and the information and the limitation of the materials produced by the native speakers become the problems. In response to the issue, the present research investigates how authentic materials are used in teaching listening. Employing a case study, this research was designed to concentrate on an EFL teacher's way of planning, designing and implementing the authentic materials to teach at eleventh grade at one private senior high school in Pekanbaru, Riau Province. The data were collected by documents, classroom observations, and interviews. The results of data analysis revealed that using authentic materials have fostered students' listening comprehension. The teacher played important role in fostering students' listening comprehension and the teacher's contribution in selecting, designing and implementing authentic materials could help the students in developing their listening comprehension. The implementation of authentic materials was run well in the classroom by following the bottom-up processing. Moreover, there is a consistency between the teacher's perspective on the use of authentic materials and the practice of teaching listening by using authentic materials in EFL classroom. Lastly, there were advantages of using authentic materials besides fostering students listening comprehension as well as the constraints during the implementation. Further suggestion is made to address classroom problems regarding the variety of materials in teaching EFL listening comprehension. ;---Bahan otentik dianggap berguna dalam mendengarkan kelas karena dapat menumbuhkan keterlibatan belajar siswa. Namun, pemilihan dan penyajian materi di kelas mendengarkan terutama dalam mengatasi kesulitan dalam menangkap makna dan informasi serta keterbatasan bahan yang diproduksi oleh penutur asli menjadi masalah. Menanggapi masalah ini, penelitian ini menyelidiki bagaimana bahan otentik digunakan dalam mengajar mendengarkan. Dengan menggunakan studi kasus, penelitian ini dirancang untuk berkonsentrasi pada cara guru EFL dalam merencanakan, merancang, dan mengimplementasikan materi otentik untuk mengajar di kelas sebelas di satu sekolah menengah swasta di Pekanbaru, Provinsi Riau. Data dikumpulkan dengan dokumen, observasi kelas, dan wawancara. Hasil analisis data mengungkapkan bahwa menggunakan bahan-bahan otentik telah menumbuhkan pemahaman mendengarkan siswa. Guru memainkan peran penting dalam menumbuhkan pemahaman mendengarkan siswa dan kontribusi guru dalam memilih, merancang, dan menerapkan bahan otentik dapat membantu siswa dalam mengembangkan pemahaman mendengarkan mereka. Implementasi bahan otentik dijalankan dengan baik di kelas dengan mengikuti proses bottom-up. Selain itu, ada konsistensi antara perspektif guru tentang penggunaan bahan otentik dan praktik mengajar mendengarkan dengan menggunakan bahan otentik di kelas EFL. Terakhir, ada keuntungan menggunakan bahan-bahan otentik selain membina pemahaman mendengarkan siswa serta kendala selama implementasi. Saran lebih lanjut dibuat untuk mengatasi masalah kelas mengenai berbagai bahan dalam mengajar pemahaman mendengarkan EFL